A Decomposition Analysis of Inequality in Malnutrition among under Five Children in Iran: Findings from Multiple Indicator Demographic and Health Survey, 2010 - Abdollah ALMASIAN KIA; Sahar GOODARZI; Heshmatollah ASADI; Ardeshir KHOSRAVI; Aziz REZAPOUR (Tehran University of Medical Sciences, 2019)
Background: Nutritional status at the early stages of children's lives is essential for growth and development not only in infancy but also in adult life. This study aimed to measure the inequality in malnutrition among under-five children in Iran and explore the impact of socioeconomic factors on this inequality using a regression-based decomposition approach. Methods: Data were extracted from Iran's Multiple-Indicator Demographic and Health Survey 2010. The concentration index of stunting, underweight, and wasting were applied in order to measure the magnitude of socioeconomic inequality in child malnutrition. Moreover, the concentration indices were decomposed to understand the contribution of socioeconomic variables in childhood malnutrition inequality. Results: The obtained concentration indices of stunting, underweight, and wasting were respectively -0.177, -0.092, and -0.031. Socioeconomic inequality in stunting and underweight was statistically significant, however this socioeconomic gradient was not observed in wasting. More than 50% of the inequality in stunting and about 63% of the inequality in underweight were influenced by socioeconomic status. Furthermore, maternal education was associated with 19% and 22% of inequality in stunting and underweight respectively. Conclusion: The average reduction of malnutrition indices at the national level hides the burden of malnutrition among children in poor families. If government and policymakers seek to solve this problem, they have to take direct and targeted actions to eliminate the existing inequalities in the socioeconomic determinants associated with malnutrition.